The worst off in Europe - country differences and trends over time in (low) life satisfaction - Frech, Johannes; Fors Connolly, Filip; Hjerm, Mikael (International journal of sociology, 2024)
In recent years, policymakers and researchers have shown increased interest in subjective well-being across countries. While previous research primarily focused on country averages, measuring the distribution of subjective well-being through standard deviation has become more frequent. This article introduces a new approach to assess subjective well-being: focusing on the "worst off," or the group with the lowest levels of well-being. Based on several ethical and political theories, this measure is deemed the most relevant when assessing well-being levels in society. The study constructs new measures of low subjective well-being (the bottom 10%) to evaluate differences across countries, changes over time, and associations with economic growth, using data from 33 European countries from 2002 to 2018. The findings indicate significant variations in well-being for the worst off across countries, with improvements observed in almost all countries studied, particularly in Poland, Germany, and the Czech Republic. Improvements are generally larger for the worst off compared to the general population. Furthermore, both GDP per capita and financial satisfaction are positively associated with the subjective well-being of the worst off, both over time and when countries are compared cross-sectionally. The implications of these findings for future research and benchmarking quality of life are discussed.